Activities of the Emergency Service of Boy-Scouts and Girl-Scouts of the Małopolska District in the Scope of Assistance for War Refugees from Ukraine in the Light of Messages From the Scout Headquarters and Scouts Reports - Baziur Grzegorz (2024)
The main purpose of the article is to show examples of help from the Polish authorities and society for Ukrainian war refugees by using the example of the activity of the Emergency Service of Boy-Scouts and Girl-Scouts (PHiH) of the Polish Scouting Association (ZHR) after the Russian aggression against Ukraine, undertaken on February 24, 2022.